An Alternative in Determining the Best Wood for Guitar Materials Using MOORA Method - Tundo, Tundo; Nugroho, Wisnu Dwi (IJID (International Journal on Informatics for Development), 2020)
This study aims to assist wood craftsmen in Dongkelan, Krapyak, Yogyakarta in determining the best wood to be used as guitar material, because there are frequent complaints from buyers that the materials used as guitar materials are rotten quickly and are dull in terms of color. Based on these problems, a solution is sought using the Multi Objective Optimization on the basis of Ratio Analysis (MOORA) decision support system method, and is assisted by experts in determining the right criteria related to determining the best wood used in making guitar materials, after a long time discussing the correct criteria were found based on the problem, in the form of criteria for wood strength, wood grain, texture, and wood weight. All of these criteria are then processed using the MOORA decision support system method. After processing, the best results are obtained. The right wood for guitar making is ebony with 23.6831 results occupying the first rank. Proving the results of the MOORA decision support system method, a questionnaire was carried out directly to several guitar makers with a total of 14 people, resulting in an accuracy of 85.71% which means that it has significant verification, that ebony wood is best used as a guitar-making material